2019
DOI: 10.12693/aphyspola.136.299
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence of Annealing Temperature on Mechanisms of Charge Carrier Transfer in GaAs in the Aspect of Possible Applications in Photovoltaics

Abstract: The article presents the results of investigations of the mechanisms of electric charge transfer in gallium arsenide subjected to poly-energic implantation with hydrogen ions, as a potential base material dedicated for photovoltaic applications. The main objective of the research was to determine the relationship between the temperature of isochronous postimplantation annealing and the probability of electron jumping between energy levels as a function of operating temperature and to test the possibility of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Other advantages to be mentioned are: controllable bandwidth and desirable optical absorption [2]. GaAs is a material that could be successfully used as a base of photovoltaic cells -it is reported that the material could increase substantially the efficiency of such cells up to 44.7% [6], as there is a strict correlation between the solar cell efficiency and the value of the band gap [7]. It is well known that using of ion implantation technology results in creation of additional energy levels, also in GaAs [8].…”
Section: Introductionmentioning
confidence: 99%
“…Other advantages to be mentioned are: controllable bandwidth and desirable optical absorption [2]. GaAs is a material that could be successfully used as a base of photovoltaic cells -it is reported that the material could increase substantially the efficiency of such cells up to 44.7% [6], as there is a strict correlation between the solar cell efficiency and the value of the band gap [7]. It is well known that using of ion implantation technology results in creation of additional energy levels, also in GaAs [8].…”
Section: Introductionmentioning
confidence: 99%
“…One way to increase efficiency is to create additional energy levels. The work carried out for many years by our research team in this area has allowed us to gather experience in this field, which has been quoted in numerous articles [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%